Algumas técnicas utilizando o software GeoGebra no processo de resolução de problemas geométricos do ensino básico: situações de máximos e mínimos e lugares geométricos - Beltrami, Reginaldo Silva (Universidade Federal de Roraima, 2022)
In view of the changes over time, from the technological advances and contained in all sectors, human life has been affected significantly. In particular, one seeks to make use of these new technologies, aiming to motivate learning of the individual and the methods used in education. And, with regard to consolidation in the educational process, the dynamic software are designed to help traditional models of education and contribute to the development of the educational setting. In basic education, it is expected that students know how to use these technological tools for better understanding and visual- ization of geometric problems. Thus, the main objective of this dissertation is to present some techniques that contribute to facilitating the understanding of geometric problems related to the flat geometry approach to changing situations using real functions, the concept of locus and GeoGebra software. Finally, we present a collection of ten related geometric problems more closely with the concepts of locus, maximum and minimum, in which will serve as a reference for teachers and students who wish to explore this powerful tool called GeoGebra.